Randomized Clinical Trial Comparing the Effects of the Myofunctional Trainer and the Twin Block on the Development of Class II Division I Malocclusion (Journal of Pharmaceutical Negative Results, 2023)
The myofunctional trainer T4 KTM and twin block were compared for dentoalveolar effects in children with class II division I malocclusion. Thirty healthy 9–12-year-olds with Angle's class II division I malocclusion due to mandibular retrusion participated in a two-arm randomized comparative clinical experiment. Group 1: T4k, Group 2: twin block. 9 months of 4-weekly follow-up. For measurements and comparison, postoperative cephalometric X-rays, study casts, and pictures were acquired. The twin block revealed a statistically significant decrease in the overjet (p < 0.0001), a substantial reduction in the (p = 0.02), and a significant rise in the LAP. Twin block outperformed T4K appliance in dentoalveolar improvements towards class I occlusion.